Overexpression of Mucin 1 Suppresses the Therapeutical Efficacy of Disulfiram against Canine Mammary Tumor - Ying Zhao (Animals, 2021)
Mucin 1 (MUC1), a transmembrane protein, is closely associated with the malignancy and metastasis of canine mammary tumors; however, the role of overexpressed MUC1 in the development of cancer cells and response to drug treatment remains unclear. To address this question, we developed a new canine mammary tumor cell line, CIPp-MUC1, with an elevated expression level of MUC1. In vitro studies showed that CIPp-MUC1 cells are superior in proliferation and migration than wild-type control, which was associated with the upregulation of PI3K, p-Akt, mTOR, Bcl-2. In addition, overexpression of MUC1 in CIPp-MUC1 cells inhibited the suppressing activity of disulfiram on the growth and metastasis of tumor cells, as well as inhibiting the pro-apoptotic effect of disulfiram. In vivo studies, on the other side, showed more rapid tumor growth and stronger resistance to disulfiram treatment in CIPp-MUC1 xenograft mice than in wild-type control. In conclusion, our study demonstrated the importance of MUC1 in affecting the therapeutical efficiency of disulfiram against canine mammary tumors, indicating that the expression level of MUC1 should be considered for clinical use of disulfiram or other drugs targeting PI3K/Akt pathway.